EFEKTIFITAS PEMBELAJARAN DARING BERBASIS EDMODO DALAM MENINGKATKAN PEMAHAMAN SISWA MATERI TURUNAN FUNGSI DI MASA COVID-19 - Fitriyani Hali; Farman Farman (Jurnal Karya Pendidikan Matematika, 2021)
This study aims to determine the effectiveness of Edmodo-based online learning in improving the understanding of class XI students of SMA Negeri 8 Kendari on derivative functions during the covid-19 period. The population in this study were all students of Class XI SMA Negeri 8 Kendari. The sampling technique used is purposive sampling, namely students of class XIB. The research instrument used in this study was a student's concept understanding test. The study uses data analysis techniques, namely descriptive analysis and inferential analysis. The results showed that (1) the average ability of students to understand concepts in the derivative function material has increased. The average ability to understand concepts at the time of the pretest was in the poor category (42.38) increased in the posttest to the medium category (72.85), (2) Edmodo-based online learning was effectively used in improving students' understanding of function derivative materials during the covid-19.